Molecular modeling of bacterial polysaccharide antigens to inform future vaccine development - Hlozek, Jason (Department of Chemistry, 2021)
Polysaccharide conjugate vaccines have been pivotal in reducing the prevalence and severity of bacterial infectious diseases worldwide, preventing countless deaths. The effectiveness of a vaccine can be extended if the selected vaccine strains in a multivalent vaccine cross-protect against non-vaccine strains. Detailed knowledge of antigen structure and conformation is required for vaccine components to be rationally selected. However, experimental methods may not be able to ascertain the conformations of polysaccharide chains. To address this, molecular dynamics simulations can provide key theoretical insights on molecular conformation to rationalize cross-protection data and inform vaccine development. In this work, we use molecular dynamics to investigate the conformations of glycan antigens of Neisseria meningitidis and Shigella flexneri bacteria - causative agents of meningitis and diarrheal disease. For N. meningitidis, our modeling indicates that serogroup A is unlikely to cross-protect against serogroup X infection, justifying the inclusion of serogroup X in future multivalent meningococcal vaccines. We also find that a chemically-stable carba-analogue of serogroup A has significant conformational differences to the native serogroup A chain, which does not support its use as a suitable serogroup A vaccine replacement. Our simulations of S. flexneri glycan antigens (serogroups Y, 2, 3, and 5) identify heuristics for the effects of substitution on backbone conformation and supports a proposed vaccine containing serotypes 2a (with O-acetylation) and 3a that will provide broad crossprotection. These findings can guide the rational selection of vaccine components to result in next-generation vaccines with greater cost-effectiveness and improved disease coverage.